2020
DOI: 10.3390/app10082711
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Students’ Behavioral Intention to Use Open Source Software: A Combined View of the Technology Acceptance Model and Self-Determination Theory

Abstract: This study focuses on students’ behavioral intention to use Open Source Software (OSS). The article examines how students, who were trained in OSS, are motivated to continue using it. A conceptual model based on Self-Determination Theory and the Technological Acceptance Model (TAM) was defined in order to test the behavioral intention to use OSS, comprising six constructs: (1) autonomy, (2) competence, (3) relatedness, (4) perceived ease of use, (5) perceived usefulness and (6) behavioral intention to use. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 96 publications
9
29
1
Order By: Relevance
“…Consistent with prior studies (Racero et al, 2020;Rizun and Strzelecki, 2020;Zardari et al, 2021), the extended TAM used in this study successfully explained the distance learning process of adoption, as seen by Indonesian sports science students. The specific major, sports science, involved in this study helps us focus on a certain field of study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with prior studies (Racero et al, 2020;Rizun and Strzelecki, 2020;Zardari et al, 2021), the extended TAM used in this study successfully explained the distance learning process of adoption, as seen by Indonesian sports science students. The specific major, sports science, involved in this study helps us focus on a certain field of study.…”
Section: Discussionsupporting
confidence: 86%
“…6 ( Racero et al, 2020) The suggested structural model was tested using Lisrel software with a total of 352 valid replies.…”
Section: Preliminary Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environment of education and sociocultural trends of the modern educational system undergone transformations (Castro-Bedrin et al, 202;Haidi and Rabiman, 2019;Sabirova et al, 2019;Racero et al, 2020;Zamaletdinova et al, 2019). Research (including Gartner, OECD, WEF) indicates that in the coming decade many new job categories will appear, partly or completely replacing existing jabs.…”
Section: Discussionmentioning
confidence: 99%
“…First, the domestic research on the perception of online entrepreneurship education platforms is enriched. Entrepreneurship education is a relatively new concept, and the rapid development of online entrepreneurship education platforms has also provided a different research dimension, research of which is still in its primary stage, focusing on the qualitative analysis of the status and the problems in this field (Han, 2020 ; Racero et al, 2020 ). Under this research background, new entrepreneurs are reluctant to participate in online entrepreneurship education, so more subjective influencing factors are proposed here to analyze their influence on the use of online entrepreneurship education platforms for new entrepreneurs.…”
Section: Introductionmentioning
confidence: 99%